Costs of joint production of ethanol and industrial sugar juice using energy beets in the Northern Plains of the United States. (10th October 2015) - Wamisho, Kassu; Ripplinger, David; De Laporte, Aaron
Abstract: This study evaluates the economic feasibility and profitability of producing industrial sugar juice and ethanol using energy beets in the Northern Plains of the United States. An enterprise budget is constructed to estimate the breakeven price of energy beets that triggers farmers to produce the crop. This breakeven price is used to estimate the long‐run breakeven prices for industrial sugar juice and ethanol. Stochastic models are developed to account for price and parameter variability in the estimation of enterprise budgets and breakeven prices. Results show that the simulated breakeven price of producing ethanol is 518 m −3 and that of industrial sugar juice is 351 t −1, using a 36 t −1 breakeven delivered cost of energy beets. Energy beet ethanol investment could be profitable at the breakeven prices of energy beets and ethanol computed, and could attract new capital investment into the ethanol industry. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd